ADOPTION OF USER SATISFACTION WITH THE UTAUT2 MODEL IN USING INDONESIA SHARIA MOBILE BANKING - Sari, Anggi Puspita; Sukardi, Budi; Abadi, Muhammad Kurnia Rahman (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
Indonesia has a large number of internet users, which at the very least indicates its enormous digital potential. Banks and other financial institutions are benefiting from improved digital offerings. This study strengthens literacy and inclusion as an effective strategy for strengthening the effects of the integrated UTAUT2 construct model with user satisfaction using Islamic mobile banking applications. Quantitative research type, with a research sample of 206 respondents as the primary data source using a questionnaire survey. Data analysis using partial regression analysis (PLS-SEM). The results prove that several factors have a positive and significant effect, namely the variables of behavioral intention, facilitating conditions, habit on user behavior and habit, hedonic motivation, and user satisfaction on behavioral intention. On the other hand, some variables do not affect, namely the variables of performance expectancy, effort expectancy, facilitating conditions, price value, and social influence on behavioral intention.